"We'd be really motivated to do something about it": A qualitative study of parent and clinician attitudes towards predicting childhood obesity in practice. Issue 2 (16th May 2022) - Canfell, Oliver J.; Littlewood, Robyn; Wright, Olivia R. L.; Walker, Jacqueline L.
Abstract: Issue addressed: In Australia, one in four (24.9%) children live with overweight or obesity (OW/OB). Identifying infants at risk of developing childhood OW/OB is a potential preventive pathway, but its acceptability is yet to be investigated in Australia. This study aimed to (1) investigate the acceptability of predicting childhood OW/OB with parents of infants (aged 0‐2 years) and clinicians and (2) explore key language to address stigma and maximise the acceptability of predicting childhood OW/OB in practice. Methods: This was a cross‐sectional and qualitative design, comprising individual semi‐structured interviews. Participants were multidisciplinary paediatric clinicians (n = 18) and parents (n = 13) recruited across public hospitals and health services in Queensland, Australia. Data were analysed under the Framework Method using an inductive, thematic approach. Results: Five main themes were identified: (1) Optimism for prevention and childhood obesity prediction, (2) parent dedication to child's health, (3) adverse parent response to risk for childhood obesity, (4) language and phrasing for discussing weight and risk and (5) clinical delivery. Most participants were supportive of using a childhood OW/OB prediction tool in practice. Parents expressed dedication to their child's health that superseded potential feelings of judgement or blame. When discussing weight in a clinical setting, the use of sensitive (ie, "overweight", "above average", "growth" versus "obesity") and positive, health‐focused language was mostly supported. Conclusions: Multidisciplinary paediatric clinicians and parents generally accept the concept of predicting childhood OW/OB in practice in Queensland, Australia. So what?: Clinicians, public health and health promotion professionals and policymakers can act now to implement sensitive communication strategies concerning weight and obesity risk.